Conflict of Norms for Plantation Transfer by the Government in the Labour Creation Law and Presidential Regulation Number 5 of 2025 - Widodo, Wahyu; Barthos, Megawati (Ridwan Institute, 2025)
The plantation sector in Indonesia has experienced significant regulatory dynamics after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Labour Creation Law into Law. The provisions in articles 110A and 110B provide administrative options for companies that have opened plantations in forest areas, namely by applying for legalization and paying administrative fines. However, Presidential Regulation Number 5 of 2025 introduces stricter sanctions in the form of land takeovers by the state without going through the administrative process regulated in the law, thus giving rise to a conflict of norms. The purpose of this study is to critically examine the contradictions between the two regulations and evaluate their impact on the legal principles of state administration, especially in the context of legal certainty and legal protection for business actors. The research method used is a normative-juridical approach through literature study and comparative analysis of relevant laws and regulations, as well as a review of administrative legal theories. The study reveals a fundamental inconsistency between the Labour Creation Law, which prioritizes administrative resolution, and Presidential Regulation 5/2025, which imposes direct land takeovers without due administrative process. This disparity creates legal uncertainty, undermines the principle of legality, and threatens the investment climate in the plantation sector. Regulatory harmonization and broad policy dissemination are needed to ensure alignment with the rule of law and promote justice for all stakeholders.